Perlindungan Hukum Terhadap Notaris Yang Telah Diberhentikan Berdasarkan Pasal 13 Undang Undang Jabatan Notaris - Maraja Malela Marpaung (Darma Cendika Catholic University, 2019)
Article 13 Notary Law governs that the notary was dismissed with disrespect by the minister because it was sentenced to imprisonment based on a court ruling that had acquired the legal force remained because of a criminal offence threatened with a prison sentence of 5 (five) years or more. The provisions of article 13 of the Notary Law are closely related to the criminal code which is the law of the event, in the provision of article 1 number 12 Criminal Procedural Law defines a legal effort i.e. the right of defendant or public prosecutor to not accept a court ruling in the form of resistance Appeals or the appeal or the criminal right to apply for a review in respect of and in the manner governed by this law. With regard to the efforts of the law and Article 13, indeed, notary still has the right to prove his innocence, in this case by submitting a review pursuant to the provisions of article 263 paragraph (1) of the criminal code. Indeed, because of the lack of harmony between the constitution as material law and the criminal code as the law of Formiil, it does not reflect a legal certainty and legal protection for notary who is litigated or is dealing with Legal issues. Furthermore, in case of notary has been disrespectfully dismissed pursuant to article 13 Notary Law, but based on the verdict of review was not guilty. The notary is entitled to claim the restoration of its rights. One of the rights that will be bound to be asked by a notary public is related to his status as a notary, meaning requesting a reappointment as a notary because it has previously been dismissed disrespectfully based on article 13 Notary Law. However, due to unregulated procedures and mechanisms for reappointment of notary public in Notary Law and related legislation, in this case it can be said as a legal void and does not reflect legal protection for A notary who is litigated or is dealing with legal issues.